2020
DOI: 10.5194/essd-2019-219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satellite-based remote sensing data set of global surface water storage change from 1992 to 2018

Abstract: Abstract. The recent availability of freely and openly available satellite remote sensing products has enabled the implementation of global surface water monitoring to a level not previously possible. Here we present a global set of satellite-derived time series of surface water storage variations for lakes and reservoirs for a period that covers the satellite altimetry era. Our goal is to promote the use of satellite-derived products for the study of large inland water bodies, and to set the stage for the exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…3. The average Pearson correlation between our Landsat-derived water volumes and published MODIS-derived estimates (Tortini et al 2020) from 1992 to 2015 for 100 reservoirs achieved 0.87, and the R values does not differ remarkably from different sizes of reservoirs.…”
Section: Validation Of Global Reservoir Storage Estimatesmentioning
confidence: 47%
“…3. The average Pearson correlation between our Landsat-derived water volumes and published MODIS-derived estimates (Tortini et al 2020) from 1992 to 2015 for 100 reservoirs achieved 0.87, and the R values does not differ remarkably from different sizes of reservoirs.…”
Section: Validation Of Global Reservoir Storage Estimatesmentioning
confidence: 47%
“…However, some of these studies used images for specific dates in different years for comparison [18][19][20] , which might lead to very different results and temporal uncertainties in SWA due to the strong seasonal dynamics and interannual variation of surface water bodies 23 , and some of these studies only focused on certain hotspots in China 21,22 . Furthermore, several studies have reported the area changes of only lakes, ponds, or reservoirs 13,[24][25][26] , but did not include other surface water bodies such as rivers and streams.…”
mentioning
confidence: 99%
“…The higher hypsometric correlation we used, the less uncertainties volume estimations would have (Crétaux et al, 2016). We selected a correlation threshold of 0.7 in this study, which is lower than Tortini et al (2020) (R ≥ 0.85) and Busker et al (2019) (R ≥ 0.9), but higher than Gao et al (2012) (R ≥0.5). The selection of an appropriate correlation threshold can also depend on the purpose of the study.…”
Section: Discussionmentioning
confidence: 99%
“…3. We investigated the influence of Landsat image quality on the volume time series estimation by comparing time series derived from images with different contamination ratios (0 %-95 %) against the MODIS-derived lake product (Tortini et al, 2020). The temporal accuracy slightly decreases as the contamination ratio increases (Table S3).…”
Section: Validation Of Global Reservoir Storage Estimatesmentioning
confidence: 99%